СИНТЕЗ ТА ДІЕЛЕКТРИЧНІ ВЛАСТИВОСТІ КЕРАМІКИ La0,67LixTi1-xAlxO3 - Plutenko, Tatiana; V'yunov, Oleg; Khomenko, Boris; Belous, Anatolii (V.I.Vernadsky Institute of General and Inorganic Chemistry, 2020)
Solid solutions of Al-doped lithium lanthanum titanates La0.67LixTi1-xAlxO3 system (where 0.15 ≤ x ≤ 0.3) have been synthesized by solid-state reaction technique. Light optical microscopy has shown that the grain size of La0.67LixTi1-xAlxO3 ceramics insignificantly increases with an increase in lithium/aluminum concentration. The materials La0.67LixTi1-xAlxO3 show very high dielectric permittivity ε΄ 104 over a relatively wide frequency range (102 ≤ f ≤ 104 Hz) with no apparent dependence on the x. The impedance spectroscopy study indicates three semicircles on Cole-Cole diagram that can be attributed to electrically different areas of ceramic’s grain.